Scalar field cosmology modified by the generalized uncertainty principle. (1st December 2015) - Paliathanasis, Andronikos; Pan, Supriya; Pramanik, Souvik
Abstract: We consider quintessence scalar field cosmology in which the Lagrangian of the scalar field is modified by the generalized uncertainty principle. We show that the perturbation terms that arise from the deformed algebra are equivalent with the existence of a second scalar field, where the two fields interact in the kinetic part. Moreover, we consider a spatially flat Friedmann–Lemaître–Robertson–Walker spacetime, and we derive the gravitational field equations. We show that the modified equation of state parameter w GUP can cross the phantom divide line; that is w GUP < −1. Furthermore, we derive the field equations in the dimensionless parameters, the dynamical system that arises is a singular perturbation system in which we study the existence of the fixed points in the slow manifold. Finally, we perform numerical simulations for some well known models and we show that for these models with the specific initial conditions, the parameter w GUP crosses the phantom barrier.